The cultural and historical landscape in 3D: A didactic project based on historical stereoscopic photography - Oliver Torelló, Joan Carles; Roman Quetglas, Júlia; Mulet Gutiérrez, Maria-Josep; Sebastián Sebastián, María; López Polín, Cristina (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This paper analyzes the results obtained in the project “The cultural and historical landscape in 3D. A didactic project based on stereoscopic photography”, whose fundamental proposal is to deepen the interpretation of the landscape through historical resources based on stereoscopy. The project has been applied to the field of higher education, with repercussions in secondary education and, in general, in citizen participation platforms (OFP). The main objective is to present didactic alternatives that promote the historical understanding of landscape and the awareness of its heritage value.